KINERJA DINAMIK JEMBATAN RANGKA BAJA YANG MENERAPKAN LEAD RUBBER BEARING (LRB) - N. Retno Setiati; Joko Purnomo; Setyo Hardono (Direktorat Bina Teknik Jalan dan Jembatan, 2022)
The application of LRB technology on bridges in Indonesia is not as popular as in developed countries, even though Indonesia is one of the countries with the highest frequency of earthquake occurrences. LRB technology is more popular in its application to building structures. However, LRB technology has been widely applied to road and bridge infrastructure, especially on toll roads. Even Indonesia has been able to produce LRB with better quality and quantity compared to other countries. This study aims to determine the performance improvement of bridges using LRB in accommodating earthquake forces. This study examines the results of bridge monitoring by replacing the placement system in the form of bearing pads with LRB. Installation of LRB is carried out on a steel frame bridge with a length of 65 meters. This load test is carried out with 4 (four) methods of loading a 6 (six)-wheel truck load. Installation of 4 accelerometer sensors (two vertical bridge directions and two bridge transverse directions) installed in the middle of the span. In addition to the installation of the accelerometer, LVDT was installed in the longitudinal direction of the bridge. Based on the results of the analysis, it is found that the natural frequency value of the upper structure the bridge does not change (that is, 4.64 Hz). There was an increase in the performance of the bridge bearing system, especially the damping time from 7.36 seconds to 4.01 seconds with the same magnitude value. Keywords: steel truss bridge, LRB, cencor, frequency, damping.